Performance improvement of III–V compound solar cells using nanomesh electrode and nanostructured antireflection structures - Jian, Li Yi; Wu, Chun Ning; Lee, Hsin Ying; Heo, Junseok; Lee, Ching Ting (Solar Energy, 2019)
To improve the conversion efficiency of InGaP/InGaAs/Ge triple-junction solar cells, AuGeNi/Au nanomesh electrode structure and TiO2 nanostructured antireflection structure were designed and fabricated. Laser interference photolithography system was used to pattern 330-nm-wide nanomesh electrode structures with various AuGeNi/Au metal line intervals. Oblique evaporation method using electron beam evaporator was used to deposit TiO2 nanorod arrays with various periods. By using the AuGeNi/Au nanomesh electrode structure with metal line interval of 100 μm, the conversion efficiency of the InGaP/InGaAs/Ge triple-junction solar cells was improved to 35.25% compared with 30.84% of that with conventional bus-bar electrode structure. By using the TiO2 nanorod array with a period of 1.00 μm to replace the TiO2/SiO2 antireflection structure, the conversion efficiency was further improved from 35.25% to 37.00%.
Keywords: Anti-reflection structures; Electrode structure; Electron beam evaporators; Laser Interference; Nano-rod arrays; Nano-structured; Oblique evaporation; Triple junction solar cells; III–V compound solar cells; Laser interference photolithography system; Nanomesh electrode structure; Nanorod array antireflection structure; Oblique evaporation method